2009
DOI: 10.1111/j.1749-6632.2009.04640.x
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in Systemic Lupus Erythematosus Patients

Abstract: This study aimed to determine the prevalence of alexithymic characteristics in patients with systemic lupus erythematosus (SLE), comparing them with a population of healthy subjects. Fifty-three SLE patients [American College of Rheumatology (ACR) criteria] and 31 healthy volunteer subjects were administered validated scales for alexithymia (Toronto alexythimia scale-20), psychopathology (brief symptom inventory; hospital anxiety and depression scale), personality dimensions (NEO five-factor inventory), and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
0
14
2
Order By: Relevance
“…1 Nevertheless, some empirical evidence from the recent literature is consistent with the direction of the hypothesis emphasizing a movement from emotion dysregulation to disease vulnerability. The works of Barbosa et al (2009Barbosa et al ( , 2011aBarbosa et al ( , 2011b investigating the relationship between alexithymia and clinical variables in a sample of patients with SLE failed to find any significant correlation. We have confirmed the same result in a recent study (Barbasio et al, 2011) that showed an absence of correlations between disease activity, cumulative damage, and alexithymia in patients with SLE.…”
Section: Limitationsmentioning
confidence: 94%
See 1 more Smart Citation
“…1 Nevertheless, some empirical evidence from the recent literature is consistent with the direction of the hypothesis emphasizing a movement from emotion dysregulation to disease vulnerability. The works of Barbosa et al (2009Barbosa et al ( , 2011aBarbosa et al ( , 2011b investigating the relationship between alexithymia and clinical variables in a sample of patients with SLE failed to find any significant correlation. We have confirmed the same result in a recent study (Barbasio et al, 2011) that showed an absence of correlations between disease activity, cumulative damage, and alexithymia in patients with SLE.…”
Section: Limitationsmentioning
confidence: 94%
“…In particular, recent data suggest that a disturbance in affect regulation may be a key feature in SLE, in that it may increase perceived stress and influence the intensity or the duration of physiological stress responses (Barbosa et al, 2009(Barbosa et al, , 2011a(Barbosa et al, , 2011b.…”
mentioning
confidence: 99%
“…In a study on 53 SLE, Barbosa et al described a positive correlation between alexithymia and psychopathological symptoms as depression, anxiety, psychoticism, neuroticism and a negative correlation with quality of life domains as pain, vitality and general health perception. The authors did not find any relationship between alexithymia and SLE disease parameters as disease activity or damage [17][18][19].…”
Section: Rheumatology: Current Researchmentioning
confidence: 78%
“…2 In the SLE, there is a high prevalence of non-optimal levels of vitamin D. A prevalence of 25 (OH) D insufficiency of 15% to 75% is reported. 3 Objectives: To determine the relationship between vitamin D levels and disease activity in SLE. Methods: It is a prospective, cross-sectional study, in all patients who attended the rheumatology clinic of the Hospital Docente Padre Billini in the period August -October 2017, where the levels of vitamin D and activity of the disease were measured with SELENA-SLEDAI (£3 without activity, 3-12 moderate activity,!12 high activity).…”
mentioning
confidence: 99%
“…Vitamin D deficiency is defined as serum levels of 25 (OH) D<10 ng/ ml, insufficiency levels serum levels of 25 (OH) D of <30 ng/ml. 3 Inclusion criteria: all patients with at least 18 years of age who met the SLE SLICC 2012 classification criteria were included with determination of vitamin D and calcium. Results: 45 patients who met criteria SLE SLICC 2012 were included.…”
mentioning
confidence: 99%